(untitled) (MAUSAM, 1983)
A study is made of the sea surface pressure (SSP) and sea surface temperature (SST) patterns and distribution of cloudiness for different months over Indian Ocean (north of 15 S and between 40° E and 100° E) with the help of Marine annual summary data for the years 1961, 1964,1965 and 1966. In April and May the area of major cloudiness lies to the south of the thermal ridge ex is and east or 65 E longitude over warm sea. In the months of June, July and August of good monsoon years, only one belt of major cloudiness lying over Bay of Bengal and Arabian Sea east of 65" E IS prominent, whereas In bad monsoon years two distinct belts, one lying in the northern latitudes and the other running along equatorial ocean with interlying region of lesser cloudiness are observed. The reverse happens in the month of September when only one belt IS observed In bad monsoon years.